A study on the population dynamics of hilsa, Tenualosa ilisha (Hamilton-Buchanan) in Bangladesh - RAHMAN, M A; HALDAR, G C; MILTON, D A; MAZID, M A; MIAH, M I (The Indian Journal of Animal Sciences, 2014)
The von Bertalanffy growth parameters of Tenualosa ilisha are estimated as Loo= 59.97cm and K = 0.99 yr-1. The natural mortality (M) and fishing mortality (F) 'were found to be 1.41 yr-1 and 1.77yr-1, respectively. The estimated value for the exploitation level (E) was 0.56. The recruitment of this species was continuous with one major peak in one year. Emax was found to be 0.715.